Megestrol Acetate in the Treatment of Post COVID-19 Fatigue in a Patient of Advanced Cancer: A Case Report and Mini Review of Literature - Patil, Chaitanya R; Dhamne, Nilesh A; Tanawade, Prasad K; Mestri, Namrata B (Indian Journal of Medical and Paediatric Oncology, 2022)
Megestrol acetate is one of the pharmacological agents used for cancer-associated fatigue. To date, there are no studies on its use in the treatment of post-COVID-19 (coronavirus disease 2019) fatigue. So, we report a case of metastatic carcinoma lung with a partial response with three cycles of palliative chemotherapy. He was contracted with mild COVID-19 infection post three cycles of his chemotherapy. Post this episode, fatigue was his main and most troublesome symptom. After a thorough clinical history, physical examination, and investigations, type 2 post-COVID-19 syndrome was diagnosed. After explaining the risks and benefits, we started the patient on low-dose megestrol acetate (160 mg/d per oral) with low to moderate benefits. However, upon increasing the dose to 480 mg/d, the benefit on the subjective quality of life was significant. Studies with a larger sample and randomized controlled trials have to be conducted to substantiate the hypothesis and actual effect of megestrol acetate in the treatment of post-COVID-19 fatigue.
Keywords: post COVID-19 syndrome; advanced cancer; fatigue; megestrol acetate